The Role of Local Wisdom in the Development of Aquaculture: A Qualitative Approach - Nurul Fadhilah; Naela Mikyalul Faizah; Fitri Arianti Saputri; Amalia Tasya (Aquapolis, 2024)
Aquaculture is an important sector in meeting global food needs and maintaining food security, especially in countries with coastal areas. As the largest archipelagic country, Indonesia has great potential in aquaculture that supports domestic food security and exports. However, the sector faces complex challenges such as climate change and environmental degradation. Sustainable management and integration of local wisdom, such as the "sasi" system, are important solutions in facing this challenge. This study aims to explore the role of local wisdom in supporting sustainable aquaculture through a qualitative approach to case studies. The results of the study show that local wisdom plays an important role in maintaining the balance of the ecosystem and supporting environmental sustainability. The combination of modern technology and traditional practices is an effective strategy to create a resilient and environmentally friendly aquaculture system. This research emphasizes the importance of collaboration between the government and the community in recognizing and strengthening custom-based regulations to achieve a balance between environmental sustainability and economic resilience.